2020
DOI: 10.7160/aol.2020.1200105
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Energy Consumption and Agricultural Production on Carbon Dioxide Emissions in Portugal

Abstract: The consequences of climate change heavily influence the Mediterranean region. However, the Portuguese CO 2 emission shows a decreasing tendency, the evolution of livestock and animal production have significantly increased its level in agriculture. The article investigates the role of the agricultural output and energy consumption in the environmental pollution in Portugal. It explores the short and long-run cointegration between carbon dioxide emissions and agricultural activities such as crop production, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Many of these studies use macroeconomic variables and are applied to a set of countries (panel data) or to a country (time series). However, there are also studies applied to a specific sector such as the agricultural sector (e.g., [3][4][5]) that also validate this relationship, reaching similar conclusions.…”
Section: Introductionmentioning
confidence: 72%
“…Many of these studies use macroeconomic variables and are applied to a set of countries (panel data) or to a country (time series). However, there are also studies applied to a specific sector such as the agricultural sector (e.g., [3][4][5]) that also validate this relationship, reaching similar conclusions.…”
Section: Introductionmentioning
confidence: 72%
“…Likewise, (Waheed et al, 2018) found no causality between renewable energy consumption per worker or added value of agriculture sector in Pakistan. Regarding Portugal's case study by (Leitão & Balogh, 2020), they discovered a one-way relationship where energy consumption influenced crop production index based on ARDL modeling using time series data from 1960 to 2015 along with Autoregressive Integrated Moving Averages techniques. A global study in 127 countries found that nations with stronger governance systems had higher agricultural output compared to those with weaker institutional frameworks, even when utilizing the same input factors.…”
Section: Introductionmentioning
confidence: 99%